Understanding style : practical ways to improve your writing - Glaser, Joseph (Oxford University Press, 1999)
Style is often the most difficult issue for writers to deal with. Most people feel helpless and confused when asked to improve something they have written. In fact, key secrets to improving style often remain concealed because even the authors who write on style may not be able to explain them clearly. An ideal text for courses in advanced composition, Understanding Style uncovers some of the inherent mystery of style and explains how to craft good sentences and combine them into writing that is clear and readable. While similar books often fail to address the relationship between written style and spoken voices or to discuss the ways that writers control rhythm and emphasis--precisely the kind of issues that give style its reputation as a difficult topic--this unique book adapts the findings of modern linguistic research into detailed writing advice seldom found elsewhere. Though it emphasizes the "sound" of the written voice throughout, the text also covers diction, coherence, and sentence variety. Glaser includes numerous open-ended exercises drawn from such areas as business, history, and popular science to encourage students to practice as they learn. Each chapter concludes with a boxed summary for quick reference and a "Your Writing" prompt, asking students to apply these principles directly to their own work. The book also features a glossary of writing terms, a brief dictionary of usage, a guide to punctuation, and a detailed index. Downloadable exercises, useful writing links, and other help may be found at the author's website at